2010
DOI: 10.1021/bm100500v
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Internalization of Polymer Hydrogel Capsules by Mammalian Cells

Abstract: Polymer hydrogel capsules comprised of poly(methacrylic acid) chains and cross-linked via disulfide linkages were investigated for their cytotoxicity and mechanism of internalization in a variety of mammalian cells. The capsules were internalized by all the tested cell lines which differed in their morphology and function and over short to medium term (24 h) revealed no reduction in viability and metabolic activity of cells. The mechanism of capsule uptake was analyzed using inhibitors of various cellular entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 41 publications
6
44
2
Order By: Relevance
“…Similarly for hydrogel discs, Merkel et al demonstrated prolonged circulation for particles with diameter comparable to RBCs, as compared to smaller particles of identical composition [46]. As discussed later in this review, carrier mechanical flexibility can generally confound trends relating clearance time to particle size, where softer particles generally exhibit longer circulation times related to altered hemodynamic behavior [43, 47] and interactions with phagocytic cells [48,49]. …”
Section: Modulation Of Pharmacokinetics and Targeting By Carrier Gmentioning
confidence: 99%
“…Similarly for hydrogel discs, Merkel et al demonstrated prolonged circulation for particles with diameter comparable to RBCs, as compared to smaller particles of identical composition [46]. As discussed later in this review, carrier mechanical flexibility can generally confound trends relating clearance time to particle size, where softer particles generally exhibit longer circulation times related to altered hemodynamic behavior [43, 47] and interactions with phagocytic cells [48,49]. …”
Section: Modulation Of Pharmacokinetics and Targeting By Carrier Gmentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84][85][86] PEG corona on capsules' surface Avoiding rapid clearance following in vivo administration…”
Section: Light-responsive Releasementioning
confidence: 99%
“…To date, only limited in vitro data have been reported while barely any in vivo data on their performance are available. Efficient uptake of redox-responsive capsules by various cell types has been demonstrated [81]. Yan and colleagues demonstrated that thiol groups and disulfide bonds in the poly(methacrylic acid) (PMA SH ) capsules enhance cellular association and uptake via exofacial thiols on the cell membrane.…”
Section: Redox-responsive Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Zelikin et a. have synthesized a nanostructural material in form of polymer hydrogel capsules comprised of PMA chains and cross-linked via disulfide linkages (PMA HC) [45]. They investigated the interactions of PMA HC with a range of mammalian cells and demonstrated that the capsules were effectively internalized by all mammalian cells lines, both adherent and nonadherent.…”
Section: Covalent Attachment Of Polymermentioning
confidence: 99%